Agriculture Non-Point Source Pollution Control - Cestti, Rita (Washington, DC: World Bank, 2013)
The Chesapeake Bay is the largest and historically most productive estuary in the United States. It is approximately 200 miles long and 35 mile wide at it broadest point. The Bay's watershed includes parts of six states (Delaware, Maryland, New York, Pennsylvania, Virginia, West Virginia, and the entire District of Columbia. This area encompasses 64,000 square-miles, 150 major rivers and streams and has a population of 15.1 million people. It receives half of its water from the Atlantic Ocean; the rest from rivers, streams and groundwater sources. Fifty percent of the freshwater coming into the Bay comes from the Susquehanna River, which starts in New York State and flows through Pennsylvania and Maryland. The Chesapeake Bay supports 3,600 species of plants, fish and animals. It is home to 29 species of waterfowl, a major resting ground along the Atlantic Migratory Bird Flyway, and provides winter nesting for over one million waterfowl. After years of decline, the Bay still supports number of commercial and recreational fisheries, producing about 500 million pounds of seafood per annum. Over the years as its population the watershed grew, use of agricultural chemicals became widespread and livestock numbers increased, the water quality in the Bay declined. Nutrients, sediments and toxic chemicals flowing into the Bay were decreasing dissolved oxygen, increasing turbidity, killing-off sea grasses and producing diseases in fish and shellfish. Research undertaken in the late 1970s and early 1980s determined that the major culprits responsible for the decline of the Chesapeake Bay's health were the excess nutrient loads from municipal wastewater plants and from agriculture and residential lands, the sediment runoff from agricultural and residential construction, and the high level of toxic chemicals coming from industry and agriculture.